Biochar produced from oak sawdust by Lanthanum (La)-involved pyrolysis for adsorption of ammonium (NH4+), nitrate (NO3−), and phosphate (PO43−). (January 2015) - Wang, Zhanghong; Guo, Haiyan; Shen, Fei; Yang, Gang; Zhang, Yanzong; Zeng, Yongmei; Wang, Lilin; Xiao, Hong; Deng, Shihuai
Highlights: It was feasible to employ the LaCl3 in slow pyrolysis for producing La-biochars. Biomass pyrolysis behaviors were not significantly changed by La-involvement. Readily soluble NH4 +, NO3 − and PO4 3− releases from La-biochars were greatly weakened. NH4 +, NO3 − and PO4 3− maximum adsorption capacity of La-biochars was greatly improved. Abstract: A series of biochars were prepared by pyrolyzing oak sawdust with/without LaCl3 involvement at temperature of 300–600 °C, and approximate and ultimate analyses were carried out to check their basic characteristics. Meanwhile, the releases of readily soluble NH4 +, NO3 − and PO4 3− from biochars and the adsorption of NH4 +, NO3 − and PO4 3− by biochars were investigated. Results indicated that the involvement of LaCl3 in pyrolysis could advance the temperature of maximum mass loss by 10 °C compared with oak sawdust (CK), and potentially promoted biochar yield. Overall, the releases of readily soluble NH4 +, NO3 − and PO4 3− from biochars were negatively related to pyrolysis temperature, and the releases were greatly weakened by La-biochars. Additionally, the adsorption to NH4 + can be promoted by the biochars produced at low temperature. On the contrary, the NO3 − adsorption can be improved by increasing pyrolysis temperature. The highest PO4 3− adsorption was achieved by the biochars produced at 500 °C. According to the results of adsorption isotherms, the maximum adsorption capacity of NH4 +, NO3 − and PO4 3− can be significantly promoted by 1.9, 11.2, and 4.5 folds using La-biochars. Based on the observations of FT-IR, SEM–EDS, and surface functional groups, the improvement of NH4 + adsorption was potentially associated with the existing acidic function groups (phenolic-OH and carboxyl CO). The increased basic functional groups on La-biochars were beneficial to improve NO3 − and PO4 3− adsorption. Besides, PO4 3− adsorption was also potentially related to the formed La2 O3 .